Parameter-Adaptive Compensation (PAC) for Processing Underwater Selective Absorption - Liu, Junnan; Zhang, Xiaoyu (IEEE signal processing letters, 2020)
The quality of visual information of underwater images is mainly limited by selective absorption and scattering in water. Usually, most researches of underwater image recovery focus on addressing the scattering via inverting an optical model, but less on compensating for the unbalance attenuation caused by the selective absorption. For this reason, the recovery results are still subject to artifacts and color shifting. In this letter, a parameter-adaptive compensation method is proposed to mitigate the selective absorption. Different from the fixed parameter utilized compensation operations, the proposed method utilizes an adaptation parameter to compensate the attenuation. Further, a rigorous gradient relation between the dominant color channel and the compensated channel is established to avoid over-compensation or under-compensation. The final recovery results show the parameter-adaptive compensation method is beneficial to improve the visual quality and the Underwater Image Quality Measurement (UIQM) scores of recovered underwater images.